PERBANDINGAN METODE EVAPORASI POTENSIAL DI BADAN METEOROLOGI KLIMATOLOGI DAN GEOFISIKA SAWAHAN KABUPATEN NGANJUK, JAWA TIMUR - Suhartanto, Ery; Limantara, Lily Montarcih; Rossy Tamaya, Hana Arum (Jurnal Teknik Pengairan, 2020)
The research aims to at suitable empirical model for reasonable estimation of reference evaporation for Nganjuk region. In this research, the observations were recorded at Sawahan meteorological station are used to calculate the evaporation with the methods of BlaneyCriddle, Penman method, Radiation method, Turc-Langbein-Wundt method, Hamon method, Christiansen method and multiple linier regression. The results of each method compared with the results of the other and validation tests used relative error, Nash-Sutcliffe Efficiency, and Root Mean Square Error. Based on the calculate results it concluded that the appropriate method was multiple linier regression with validation test as follows: rate of relative error is 1,15, rate of Nash Sutcliffe Effiency is 0,70 and rate of Root Mean Square Error is 0,178.